Perirectal hydrogel spacer placement prior to prostate radiation therapy using a probe-mounted needle guide. (July 2021) - Meyer, Alexa R.; Dharmaraj, Divya; Harb, Rana; Pavlovich, Christian P.; Allaf, Mohamad E.; Gorin, Michael A.
Highlights: Perirectal spacer placement minimizes the risk of bowel toxicity from prostate radiation therapy. We show that a novel probe-mounted needle guide can be safely used for perirectal spacer insertion. The main advantage of this device is that it ensures needle visualization throughout the procedure. Abstract: In this report we describe our successful adoption of a single-use, probe-mounted, needle guide for perirectal hydrogel spacer placement prior to radiation therapy for prostate cancer. Use of this device eliminates the need for a mechanical stepper unit and facilitates perirectal hydrogel placement by ensuring alignment of the injection needle with the ultrasound probe.